IMPLEMENTASI PROGRAM ePPM-UKM UNTUK PENGUATAN KINERJA MANAJEMEN UKM DAN INDUSTRI KREATIF - Wahyudiono Wahyudiono; R. Agus Baktiono (EKUITAS (Jurnal Ekonomi dan Keuangan), 2020)
This study aims to examine the effect of the ePPM-SMEs implementation to the value of management capability and management performance. Furthermore, this study examines the effect of management capability towards management performance as well. This study is an explanative/ associative study which is used hypothesis testing. The study was conducted in groups of SMEs/ creative industries spread over five cities / regions in East Java. The population is determined by the criteria of SMEs/creative industry which participate in the ePPM-SMEs program as owner and being active in business for at least five years. Based on these criteria, there are 60 SMEs / creative industries who meet the criteria. Since all members of the population are members of the sample as well so this study is also called as complete enumeration method.The results of path analysis show that the ePPM-SMEs program directly and significantly affects the management capability and management performances as well as management capability towards management performances. The results of this study indicate that the structured implementation of ePPM-SMEs program produced more creative and innovative of management capability. In addition, innovative management capabilities will result to the more effective and efficient management performance. Since management capability is the main key to determine good management performance, massive support for ePPM-SMEs program will encourage creative and innovative behavior in applying management concepts and functions.